PERLINDUNGAN HUKUM TERHADAP PENGGUNA KARTU XL ATAS PRODUK YANG TIDAK SESUAIDENGAN YANG DIIKLANKAN - Sri Divia Bella; Zulfikar Jayakusuma; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Consumer products (consumer goods / services that are generally used to meet the needs of consumers) have become increasingly sophisticated both in technology and in appearance. On the other hand, people understand a consumer product as far as what the sellers / or business actors convey. High and low regarding the understanding of the quality of the product depends on the level of truth of the information conveyed by the seller / entrepreneur and the level of the consumer's ability to capture. This information can be in the form of oral or written information contained in brochures and pamphlets, labels, advertisements and so on. The materials can be so detailed that they are often "so technical" that they are not easy to digest, but some are so simple, attractive and often equipped with relevant things or descriptions such as those contained in advertisements. Advertising is one of the promotional vehicles that considered the most effective way to introduce a product to the public. However, this has a provision as a form of consumer protection. In Law Number 8 of 1999 concerning Consumer Protection in Article 10.This research uses a typology of sociological legal research or what is also called non-doctrinal legal research, which deals more specifically with the effectiveness of law. In this research, the writer uses descriptive research characteristic, because the writer describes how to protect consumers of XL card users who do not match the advertised products, and describe how the responsibility of PT XIATA for losses received by consumers.The results of the research conducted by the author are, firstly, the implementation of the implementation of the law on the implementation of consumer protection from misleading XL Provider advertising information in Pekanbaru City has not been running properly. The responsibility of PT. AXIATA for the losses suffered by consumers due to misleading advertising information does not yet exist. There should be responsibility for advertised products that are not in accordance with reality, as well as PT AXIATA's responsibility for losses received by consumers.Keywords: Consumer Protection - Not as Advertised as Appropriate